The neural correlates of emotion alignment in social interaction. (19th June 2014) - Prehn, Kristin; Korn, Christoph W.; Bajbouj, Malek; Klann-Delius, Gisela; Menninghaus, Winfried; Jacobs, Arthur M.; Heekeren, Hauke R.
Abstract: Talking about emotion and sharing emotional experiences is a key component of human interaction. Specifically, individuals often consider the reactions of other people when evaluating the meaning and impact of an emotional stimulus. It has not yet been investigated, however, how emotional arousal ratings and physiological responses elicited by affective stimuli are influenced by the rating of an interaction partner. In the present study, pairs of participants were asked to rate and communicate the degree of their emotional arousal while viewing affective pictures. Strikingly, participants adjusted their arousal ratings to match up with their interaction partner. In anticipation of the affective picture, the interaction partner's arousal ratings correlated positively with activity in anterior insula and prefrontal cortex. During picture presentation, social influence was reflected in the ventral striatum, that is, activity in the ventral striatum correlated negatively with the interaction partner's ratings. Results of the study show that emotional alignment through the influence of another person's communicated experience has to be considered as a complex phenomenon integrating different components including emotion anticipation and conformity.